2021
DOI: 10.3390/cryst11020191
|View full text |Cite
|
Sign up to set email alerts
|

Cocrystals Based on 4,4’-bipyridine: Influence of Crystal Packing on Melting Point

Abstract: The reactions of piperonylic acid (HPip) and cinnamic acid (HCinn) with 4,4’-bipyridine (4,4’-bipy) have been assayed using the same synthetic methodology, yielding two binary cocrystals with different acid:4,4’-bipy molar ratios, (HPip)(4,4’-bipy) (1) and (HCinn)2(4,4’-bipy) (2). The melting point (m.p.) of these cocrystals have been measured and a remarkable difference (ΔT ≈ 78 °C) between them was observed. Moreover, the two cocrystals have been characterized by powder X-ray diffraction (PXRD), elemental an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 59 publications
(68 reference statements)
6
9
0
Order By: Relevance
“…Although previous studies have observed PE to be an important factor in stabilizing molecular assemblies in supramolecular compounds, [39] the result presented here fall in line with studies by Taylor et al., who determined that the stability of hydrogen bonded cocrystals was unaffected by PE , [16e] and Ejarque et al. who reported a similar finding when using the melting point of cocrystals as an indicator of crystal stability [40] . Therefore, we find that PE is not a sufficient descriptor of Δ H f for predicting crystal stability.…”
Section: Resultssupporting
confidence: 92%
“…Although previous studies have observed PE to be an important factor in stabilizing molecular assemblies in supramolecular compounds, [39] the result presented here fall in line with studies by Taylor et al., who determined that the stability of hydrogen bonded cocrystals was unaffected by PE , [16e] and Ejarque et al. who reported a similar finding when using the melting point of cocrystals as an indicator of crystal stability [40] . Therefore, we find that PE is not a sufficient descriptor of Δ H f for predicting crystal stability.…”
Section: Resultssupporting
confidence: 92%
“…Melting point plays an important role in determining the purity and stability of synthetic products and materials. , Factors including crystal density, crystal packing, or included components can influence the melting point of a cocrystal. Thermogravimetric analysis (TGA) analysis was performed for GEM , AFC , BPA , and all the cocrystals to determine the decomposition temperature, as well as the temperature at which solvent molecules are liberated for the toluene solvate of 2 ·AFC·4,4′-AP· tol (see Table , as well as Figures S33–S45 in the SI).…”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26] Its modulation has enabled the enhancement of the thermal stability and processability of the determined molecules through the formation of cocrystals. [27][28][29] Indeed, our group has previously studied the formation of cocrystals based on the acid⋯amide 30 and acid⋯pyridine heterosynthons 31 and the correlation of the crystal packing with their melting point values. 31 Therefore, aiming to extend our knowledge on the structure-property relationship of cocrystals focusing on the melting point, we have selected a liquid and a solid pyridine derivative (dPy), namely 4-acetylpyridine (4-Acpy) and 2-hydroxypyridine (2-OHpy), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] Indeed, our group has previously studied the formation of cocrystals based on the acid⋯amide 30 and acid⋯pyridine heterosynthons 31 and the correlation of the crystal packing with their melting point values. 31 Therefore, aiming to extend our knowledge on the structure-property relationship of cocrystals focusing on the melting point, we have selected a liquid and a solid pyridine derivative (dPy), namely 4-acetylpyridine (4-Acpy) and 2-hydroxypyridine (2-OHpy), respectively. It should be noted that 2-OHpy exists in equilibrium with its keto form (2-pyridone, Pdon), which in the solid state is preferentially shifted to Pdon.…”
Section: Introductionmentioning
confidence: 99%